The effect of retinoic acid on non-alcoholic fatty liver disease (NAFLD) model - Ahmed Mohamed, Nawal; Buyong, Zunariah; Abdullah, Nor Zamzila; Hamdan, Asmah Hanim; Ab Rahman, Jamalludin; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Mat Harun, Noraihan; Aung, Aung Win Tun (IIUM press, 2021)
Non-alcoholic fatty liver (NAFLD) is the most common liver disease. It carries the risk of progression to more severe conditions with a limited effective treatment available. The hallmark of the disease is the accumulation of triglycerides (TG) in hepatocytes. Retinoic acid (RA), an active form of vitamin A is stored in the liver. However, its effect on NAFLD is not established. This study aimed to investigate the potential effect of RA on NAFLD in a rat model. NAFLD was induced by a high cholesterol diet (HCD). Thirty-six rats were divided into four groups, control with a normal diet, HCD treated with vehicle, HCD only, HCD received subcutaneous RA twice weekly for four weeks. The results showed that RA could reverse the increase in body weight and liver weight. It also showed a reduction in blood glucose, blood TG and TG content in hepatocytes. These results suggested that RA ameliorated the obesity of NAFLD rats and mitigated triglyceride accumulation in the liver. Therefore, this study showed the therapeutic potential of RA on NAFLD probably by reducing triglyceride deposition in hepatocytes.